A single-atom catalyst supported on SnNb 2 O 6 -gC 3 N 5 Three-dimensional composite materials, preparation methods and applications

By loading a single-atom catalyst in the three-dimensional composite of SnNb2O6 and g-C3N5, a single-atom X-SnNb2O6/g-C3N5 three-dimensional composite was solved, and the problem of severe photogenerated electron-hole recombination and weak visible light response in the application of SnNb2O6 in the field of photocatalysis was solved, high catalytic activity and good stability were achieved, and photocatalytic performance was significantly improved.

CN117019164BActive Publication Date: 2025-02-28SUZHOU UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310944957.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-28
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

The application of SnNb2O6 as a two-dimensional nanomaterial in the field of photocatalysis is limited by the serious photogenerated electron-hole recombination and weak visible light response.

Method used

By loading a single-atom catalyst into a three-dimensional composite of SnNb2O6 and g-C3N5, a single-atom X-SnNb2O6/g-C3N5 three-dimensional composite is formed, and the strong interaction between carbon and nitrogen is used to improve the catalytic performance of the material.

Benefits of technology

High catalytic activity and good stability are achieved, the recombination of photogenerated electron-hole pairs is inhibited, the electron migration rate is accelerated, and the absorption range of visible light is expanded, which significantly improves the photocatalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117019164B_ABST
    Figure CN117019164B_ABST
Patent Text Reader

Abstract

The invention discloses a three-dimensional composite material of SnNb2O6 / g-C3N5 supported by a single atom catalyst, a preparation method and an application thereof. The preparation method of SnNb2O6 / g-C3N5 comprises the following steps: dissolving a certain amount of NaCl and 3-amino-1,2,4-triazole in water, stirring and mixing them uniformly and heating them, and then heating and calcining them to obtain g-C3N5 nanorods; (adding tin niobate (SnNb2O6) to obtain a g-C3N5 nanorod); 6) Nanosheets, ultrasonically mixed and then hydrothermally treated; (9) the product after the hydrothermal treatment is vacuum dried and placed in a mixed atmosphere of H2 and Ar2, and heated and calcined to obtain a SnNb2O6 / g-C3N5 nanocomposite material. The present invention loads metal single atoms onto the SnNb2O6 / g-C3N5 nanocomposite material through the strong interaction between carbon and nitrogen to form X-SnNb2O6 / g-C3N5, where X is platinum, cobalt, iron, palladium, copper or silver.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalysis, and specifically relates to a single-atom catalyst-loaded SnNb2O6-g-C3N5 three-dimensional composite material, a preparation method and an application thereof. Background Art

[0002] With the rapid development of the global economy, the massive use of non-renewable energy such as coal and oil has brought a huge energy crisis to mankind. At the same time, it has also caused great pollution to the environment. Therefore, how to solve the shortage of energy and environmental pollution has become the main problem restricting the sustainable development of mankind. In order to achieve the goal of sustainable development of human society, the development of environmentally friendly new technologies and the search for alternative clean energy have become the most urgent tasks. Semiconductor photocatalytic technology is one of the most promising technologies to achieve the above two tasks. The core lies in the development of new and stable semiconductor photocatalytic materials.

[0003] SnNb2O6 is a typical two-dimensional nanomaterial. Its advantages lie in its unique layered structure and high stability. This unique structure enables it to successfully capture visible light, thereby undergoing visible light catalytic reactions. However, single SnNb2O6 suffers from serious photogenerated electron-hole recombination and weak visible light response, which severely limits its application in the field of photocatalysis.

[0004] Compounding semiconductors to form heterojunctions is one of the methods to improve semiconductor photocatalytic performance. Building heterojunctions can inhibit the recombination of photogenerated electron-hole pairs, accelerate the rate of electron migration, and further expand the absorption range of visible light, thereby further improving its photocatalytic performance. However, this type of catalyst is expensive and scarce, which seriously limits its further application.

[0005] Therefore, there is an urgent need to construct a low-cost, stable and highly catalytic visible light catalyst to apply it to photocatalytic degradation of organic pollutants, photocatalytic decomposition of water for hydrogen evolution, photocatalytic CO2 reduction and photocatalytic removal of NOx. Single-atom catalysts are formed by loading metal atoms onto suitable carriers. In this process, the material is anchored by the carrier in the form of single atoms, and then electrons are exchanged with the carrier to form single-atom active sites, thereby improving the performance of the material. At the same time, single-atom catalysts have the advantages of both homogeneous catalysts and heterogeneous catalysts, which makes it possible to develop more efficient heterogeneous catalysts. Summary of the invention

[0006] The purpose of the present invention is to provide a single-atom catalyst-supported SnNb2O6-g-C3N5 three-dimensional composite material, a preparation method and an application thereof, so as to solve the above-mentioned problems.

[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a three-dimensional SnNb2O6-g-C3N5 composite material supported by a single atom catalyst, the specific steps of which are as follows:

[0008] Step 1: dissolving a certain amount of NaCl and 3-amino-1,2,4-triazole in water, stirring and mixing them evenly, and then heating and calcining them to obtain g-C3N5 nanorods;

[0009] Step 2: Add SnNb2O6 nanosheets, mix evenly by ultrasonication, and then perform hydrothermal treatment;

[0010] Step 3: After the hydrothermal treatment, the product is vacuum dried and placed in a mixed atmosphere of NH3 and Ar2, and heated and calcined to obtain a SnNb2O6 / g-C3N5 nanocomposite material.

[0011] Step 4: Add the SnNb2O6 / g-C3N5 nanocomposite material obtained in step 3 to the X precursor solution, perform vacuuming, stirring reaction and photodeposition, and obtain a single-atom X-SnNb2O6 / g-C3N5 nanocomposite material.

[0012] Preferably, in step 1, the amounts of NaCl and 3-amino-1,2,4-triazole are 10-15 g and 1-2 g, respectively.

[0013] Preferably, in step 1, the heating temperature is 60-80° C., the calcination temperature is 300-550° C., and the heating time is 3-5 h.

[0014] Furthermore, in step 1, the product is dried by alternately washing with ethanol and water and then vacuum drying.

[0015] Preferably, in step 2, the mass ratio of g-C3N5 to SnNb2O6 is 1: 0.5-4, the hydrothermal reaction temperature is 160-200°C, the hydrothermal time is 8-16 h, and the ultrasonic treatment time is 2-8 h.

[0016] Preferably, in step three, in the mixed atmosphere of H2 and Ar2, the volume ratio of H2 to Ar2 is 1: 0.5-2, the calcination temperature is 100-200° C., and the heating time is 1-3 h.

[0017] Preferably, X is one or a combination of platinum, cobalt, iron, palladium, copper and silver, and the mass ratio of SnNb2O6 / g-C3N5 to metal X in the single-atom X-SnNb2O6 / g-C3N5 nanocomposite material is 0.02:1-10.

[0018] Preferably, in step 4, the X precursor solution is chloroplatinic acid, palladium chloride, cobalt nitrate, copper acetate or silver nitrate solution, and the concentration of the X precursor solution is 5-10 mol / L.

[0019] Furthermore, a circulating cooling water system is used to keep the material at a constant temperature.

[0020] Furthermore, the constant temperature is 15-50°C and the time is 2-12 h.

[0021] Furthermore, the constant temperature is preferably 25° C. and the time is 2-6 h.

[0022] A single-atom catalyst-supported SnNb2O6 / g-C3N5 three-dimensional composite material, characterized in that it is prepared by the preparation method described in any one of claims 1 to 8.

[0023] Application of a single-atom catalyst-loaded SnNb2O6 / g-C3N5 three-dimensional composite material in visible light photocatalysis.

[0024] The technical effects and advantages of the present invention are as follows: a single-atom X-SnNb2O6 / g-C3N5 three-dimensional composite material is formed by loading a single metal atom onto SnNb2O6 / g-C3N5 through the strong interaction between carbon and nitrogen. The above-mentioned preparation method is simple to operate, has mild conditions, a fast reaction rate and low cost, and is suitable for mass production; the prepared single-atom X-SnNb2O6 / g-C3N5 three-dimensional composite material has high catalytic activity and good stability, and the composite material forms a heterojunction, inhibits the recombination of photogenerated electron-hole pairs, accelerates the rate of electron migration, and can further expand the absorption range of visible light, thereby further improving its photocatalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron microscope (SEM) image of the SnNb2O6 / g-C3N5 nanocomposite material prepared in the present invention;

[0026] Figure 2 Transmission electron microscope (TEM) image of the SnNb2O6 / g-C3N5 nanocomposite prepared by the present invention ( Figure 2 a) and high-resolution transmission electron microscopy (HRTEM) images ( Figure 2 b);

[0027] Figure 3 Transmission electron microscope (TEM) image of the Pt-SnNb2O6 / g-C3N5 three-dimensional composite material prepared by the present invention ( Figure 3 Middle left) and high-resolution transmission electron microscopy (HRTEM) images ( Figure 3 Center right);

[0028] Figure 4 The photocatalytic CO2 reduction performance comparison chart of g-C3N5, SnNb2O6, and SnNb2O6 / g-C3N5 nanocomposite materials;

[0029] Figure 5 The photocatalytic hydrogen evolution performance diagram of g-C3N5, SnNb2O6, SnNb2O6 / g-C3N5, Pt-g-C3N5 and Pt-SnNb2O6 / g-C3N5 three-dimensional composite materials ( Figure 5 Comparison of photocatalytic hydrogen evolution rate (a) and ( Figure 5 (b)

[0030] Figure 6 This is a comparison chart of the photocatalytic CO2 reduction performance of g-C3N5, SnNb2O6, and Pt-SnNb2O6 / g-C3N5 three-dimensional composite materials.

[0031] Figure 7 This is a comparison chart of the photocatalytic performance of g-C3N5, SnNb2O6, and SnNb2O6 / g-C3N5 three-dimensional composite materials for organic pollutants.

[0032] Figure 8 This is a comparison chart of the photocatalytic antibiotic degradation performance of g-C3N5, SnNb2O6, and SnNb2O6 / g-C3N5 three-dimensional composite materials. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The present invention provides Figure 1 - Figure 6 The preparation method of a single-atom catalyst-supported SnNb2O6 / g-C3N5 three-dimensional composite material shown in the figure is as follows:

[0035] Step 1: dissolving a certain amount of NaCl and 3-amino-1,2,4-triazole in water, stirring and mixing them evenly, and then heating and calcining them to obtain g-C3N5 nanorods;

[0036] Step 2: Add SnNb2O6 nanosheets, mix evenly by ultrasonication, and then perform hydrothermal treatment;

[0037] Step 3: vacuum drying the product after hydrothermal treatment, placing it in a mixed atmosphere of NH3 and Ar2, and heating and calcining to obtain SnNb2O6 / g-C3N5 nanocomposite material;

[0038] Step 4: Add the SnNb2O6 / g-C3N5 nanocomposite material obtained in step 3 to the X precursor solution, perform vacuuming, stirring reaction and photodeposition, and obtain a single-atom X-SnNb2O6 / g-C3N5 nanocomposite material.

[0039] Specifically, in step 1, the amounts of NaCl and 3-amino-1,2,4-triazole are 10-15 g and 1-2 g, respectively.

[0040] Specifically, in step 1, the heating temperature is 60-80° C., the calcination temperature is 300-550° C., and the heating time is 3-5 h.

[0041] Furthermore, in step 1, the product is dried by alternately washing with ethanol and water and then vacuum drying.

[0042] Specifically, in step 2, the mass ratio of g-C3N5 to SnNb2O6 is 1: 0.5-4, the hydrothermal reaction temperature is 160-200°C, the hydrothermal time is 8-16 h, and the ultrasonic treatment time is 2-8 h.

[0043] Specifically, in step three, in the mixed atmosphere of H2 and Ar2, the volume ratio of H2 to Ar2 is 1: 0.5-2, the calcination temperature is 100-200° C., and the heating time is 1-3 h.

[0044] Specifically, in step 4, X is one or a combination of platinum, cobalt, iron, palladium, copper and silver, and the mass ratio of SnNb2O6 / g-C3N5 to metal X in the single-atom X-SnNb2O6 / g-C3N5 nanocomposite material is 0.02:1-10.

[0045] Specifically, in step 4, the X precursor solution is chloroplatinic acid, palladium chloride, cobalt nitrate, copper acetate or silver nitrate solution, and the concentration of the X precursor solution is 5-10 mol / L.

[0046] Specifically, the method further includes the steps of solid-liquid separation after the stirring reaction, and water washing and alcohol washing of the separated solid.

[0047] Furthermore, a circulating cooling water system is used to keep the material at a constant temperature.

[0048] Furthermore, the constant temperature is 15-50°C and the time is 2-12 h.

[0049] Furthermore, the constant temperature is preferably 25° C. and the time is 2-6 h.

[0050] A single-atom catalyst-supported SnNb2O6 / g-C3N5 three-dimensional composite material, characterized in that it is prepared by the preparation method described in any one of claims 1 to 8.

[0051] Application of a single-atom catalyst-loaded SnNb2O6 / g-C3N5 three-dimensional composite material in visible light photocatalysis.

[0052] Working principle:

[0053] Example 1: Preparation of g-C3N5 nanomaterials

[0054] (1) Weigh 1.5-2 g of 3-amino-1,2,4-triazole and add it to NaCl solution (10-15 g NaCl dissolved in 30-60 mL H2O) and stir evenly;

[0055] (2) The mixed solution was then evaporated to dryness in a water bath at 80-100°C and dried at 60-80°C for 12-14 h to ensure that no water remained. The resulting white solid was then ground into powder and transferred to a muffle furnace at 10°C min −1 Heat to 500-550°C at a heating rate of 100°C and keep at this temperature for 3-5 hours. Then cool naturally to room temperature.

[0056] (3) The obtained brown product was washed alternately with ethanol and deionized water for multiple times to remove unreacted NaCl crystals and dried at 60 °C for 12 h. The obtained brown product was g-C3N5 nanomaterial.

[0057] Example 2: Preparation of g-C3N5 nanomaterials

[0058] Add equal amounts of 3-amino-1,2,4-triazole and cyanuric acid to 100-150 mL of ethanol and stir for 0.5-2 h. Then transfer the mixed solution to a 200 mL hydrothermal reactor and hydroheat at 100-180 °C for 10-12 h. Then collect the obtained white mixed solution by centrifugation and freeze-dry. Finally, grind the obtained white solid into powder and transfer it to a muffle furnace at 5 °C min −1 The mixture was heated to 500-550°C at a heating rate of 100°C and kept at this temperature for 3-5 h. The mixture was then cooled naturally to room temperature. The obtained brown powder was the g-C3N5 nanomaterial.

[0059] Example 3: Preparation of g-C3N5 nanomaterials

[0060] 3-amino-1,2,4-triazole, cyanuric acid and salicylic acid were added to 100-150 mL ethanol in a ratio of 1:1:0.8 and stirred for 1-5 h. The mixed solution was then transferred to a 200 mL hydrothermal kettle and hydrothermaled at 100-180 °C for 10-12 h. The collected white mixed solution was then washed and dried under vacuum. The obtained white solid was finally ground into powder and transferred to a muffle furnace at 5 °C min −1 The mixture was heated to 500-550°C at a heating rate of 100°C and kept at this temperature for 3-5 h. The mixture was then cooled naturally to room temperature. The obtained brown powder was the g-C3N5 nanomaterial.

[0061] Example 4: Preparation of g-C3N5 nanomaterials

[0062] 3-amino-1,2,4-triazole, cyanuric acid and salicylic acid were added to 100-150 mL ethanol in a ratio of 1:1:0.8 and stirred for 1-5 h. The mixed solution was then transferred to a 200 mL hydrothermal kettle and hydrothermalized at 100-180 ° C for 10-12 h. The collected white mixed solution was then washed and dried under vacuum. The mixture was then calcined at 500-550 ° C for 3-5 h in a mixed atmosphere of H2 and Ar2 (the volume ratio of H2 and Ar2 was 2:1). The brown powder obtained was the g-C3N5 nanomaterial.

[0063] Example 5: Preparation of g-C3N5 nanomaterials

[0064] 3-amino-1,2,4-triazole, cyanuric acid and salicylic acid were added to 100-150 mL ethanol in a ratio of 1:1:0.8 and stirred for 1-5 h. The mixed solution was then transferred to a 200 mL hydrothermal kettle and hydrothermalized at 100-180 ° C for 10-12 h. The collected white mixed solution was then washed and dried under vacuum. The mixture was then calcined at 500-550 ° C for 3-5 h in a mixed atmosphere of H2 and Ar2 (the volume ratio of H2 and Ar2 was 1:1). The brown powder obtained was the g-C3N5 nanomaterial.

[0065] Example 6: Preparation of SnNb2O6 / g-C3N5 Nanomaterials

[0066] 0.01-0.08 g SnNb2O6 was added to 20-40 mL water and ultrasonicated for 30 min, then 0.2 g of g-C3N5 nanorods prepared in Example 1 was added and the mixed solution was stirred for 4-12 h and then transferred to a 200 mL hydrothermal reactor and hydrothermaled at 100-180°C for 10-12 h, then centrifuged to obtain the mixed solution and dried. The obtained powder is SnNb2O6 / g-C3N5 nanomaterial.

[0067] The SnNb2O6 / g-C3N5 nanomaterial prepared in this example was characterized by scanning electron microscopy and transmission electron microscopy. The characterization results are as follows: Figure 1 and Figure 2 shown.

[0068] Example 7: Preparation of SnNb2O6 / g-C3N5 Nanomaterials

[0069] 0.01-0.08 g SnNb2O6 was added to 20-40 mL water and ultrasonicated for 30 min, then 0.2 g g-C3N5 nanorods prepared in Example 2 were added and the mixed solution was stirred for 4-12 h and then transferred to a 200 mL hydrothermal reactor and hydrothermaled at 100-180°C for 10-12 h, then centrifuged to obtain the mixed solution and dried. The obtained powder is SnNb2O6 / g-C3N5 nanomaterial.

[0070] Example 8: Preparation of SnNb2O6 / g-C3N5 Nanomaterials

[0071] 0.01-0.08 g SnNb2O6 was added to 20-40 mL water and ultrasonicated for 30 min, then 0.2 g g-C3N5 nanorods prepared in Example 3-4 were added and the mixed solution was stirred for 4-12 h and then transferred to a 200 mL hydrothermal reactor and hydrothermaled at 100-180°C for 10-12 h, then the mixed solution was collected by centrifugation and dried. The obtained powder is SnNb2O6 / g-C3N5 nanomaterial.

[0072] Example 9: Preparation of Pt-g-C3N5 Nanocomposite Material

[0073] 0.02 g of the g-C3N5 nanomaterial prepared in Example 1 was weighed and added to a mixed solution of 20 mL H2O and 10 mL triethanolamine. Then a certain amount of H2PtCl6·6H2O (10 mg·mL -1) Add a certain amount of ethylene glycol. Then photodeposit the mixed solution under vacuum for 2-5 h, then wash and collect the mixed solution and dry it. The obtained powder is Pt-g-C3N5 nanomaterial.

[0074] Example 10: Preparation of Pt-SnNb2O6 / g-C3N5 three-dimensional composite material

[0075] 0.02 g of SnNb2O6 / g-C3N5 nanomaterial prepared in Example 6 was weighed and added to a mixed solution of 20 mL H2O and 10 mL triethanolamine. Then a certain amount of H2PtCl6·6H2O (10 mg·mL -1) is added to a certain amount of ethylene glycol. The mixed solution is then photodeposited under vacuum for 2-5 h, and then washed, collected, and dried to obtain the mixed solution. The obtained powder is the Pt-SnNb2O6 / g-C3N5 three-dimensional composite material.

[0076] Figure 3 The TEM image of the Pt-SnNb2O6 / g-C3N5 three-dimensional composite material shows that the Pt-SnNb2O6 / g-C3N5 three-dimensional composite material is in the form of thin sheets, and the surface of the composite material prepared by the above method is smooth without obvious particles. Figure 4 This is the HRTEM image of the Pt-SnNb2O6 / g-C3N5 three-dimensional composite material. Obvious lattice fringes can be observed, but no platinum lattice fringes are found. This phenomenon indicates that platinum does not form clusters in the nanocomposite material.

[0077] Example 11: Preparation of Pt-SnNb2O6 / g-C3N5 three-dimensional composite material

[0078] 0.02 g of SnNb2O6 / g-C3N5 nanomaterial prepared in Example 6 was weighed and added to a mixed solution of 20 mL H2O and 10 mL triethanolamine. Then a certain amount of H2PtCl6·6H2O (10 mg·mL -1) A certain amount of ethylene glycol was added. The mixed solution was then transferred to a 100 mL hydrothermal reactor and hydrothermally treated at 160 ° C for 12 h, and then washed, collected, and dried to obtain the mixed solution. The obtained powder is the Pt-SnNb2O6 / g-C3N5 three-dimensional composite material.

[0079] Example 12: Preparation of Pt-SnNb2O6 / g-C3N5 three-dimensional composite material

[0080] 0.02 g of SnNb2O6 / g-C3N5 nanomaterial prepared in Example 6 was weighed and added to a mixed solution of 20 mL H2O and 10 mL triethanolamine. Then a certain amount of H2PtCl6·6H2O (10 mg·mL -1) A certain amount of ethylene glycol was added. The mixed solution was then transferred to a 100 mL hydrothermal autoclave and hydrothermally treated at 160°C for 12 h, and then the mixed solution was washed, collected and dried. The obtained powder was calcined at 600°C for 5 h in a mixed atmosphere of H2 and Ar2 (the volume ratio of H2 and Ar2 was 2:1), and the obtained powder was a Pt-SnNb2O6 / g-C3N5 three-dimensional composite material.

[0081] Example 13: Preparation of Pt-SnNb2O6 / g-C3N5 three-dimensional composite material

[0082] 0.02 g of SnNb2O6 / g-C3N5 nanomaterial prepared in Example 6 was weighed and added to a mixed solution of 20 mL H2O and 10 mL triethanolamine. Then a certain amount of H2PtCl6·6H2O (10 mg·mL -1) A certain amount of ethylene glycol was added. The mixed solution was then transferred to a 100 mL hydrothermal autoclave and hydrothermally treated at 160°C for 12 h, and then the mixed solution was washed, collected and dried. The obtained powder was calcined at 600°C for 5 h in a mixed atmosphere of H2 and Ar2 (the volume ratio of H2 and Ar2 was 1:1), and the obtained powder was a Pt-SnNb2O6 / g-C3N5 three-dimensional composite material.

[0083] Example 14: Preparation of Pt-SnNb2O6 / g-C3N5 three-dimensional composite material

[0084] Weigh 0.02 g of SnNb2O6 / g-C3N5 nanomaterial prepared in Example 6 and add it to 25 mL of H2O for ultrasonic mixing. Then add a certain amount of H2PtCl6·6H2O (10 mg·mL -1) The mixture was stirred for 4-10 h, and then washed and collected to obtain a mixed solution and dried in vacuo. The obtained powder was the Pt-SnNb2O6 / g-C3N5 three-dimensional composite material.

[0085] Example 15: Preparation of Pt-SnNb2O6 / g-C3N5 three-dimensional composite material

[0086] Weigh 0.02 g of SnNb2O6 / g-C3N5 nanomaterial prepared in Example 6 and add it to 25 mL of H2O for ultrasonic mixing. Then add a certain amount of H2PtCl6·6H2O (10 mg·mL -1) The mixture was stirred for 4-10 h, then washed and collected to obtain a mixed solution and dried in vacuo. The obtained powder was calcined at 600 °C for 5 h in a mixed atmosphere of H2 and Ar2 (the volume ratio of H2 and Ar2 was 2:1), and the obtained powder was a Pt-SnNb2O6 / g-C3N5 three-dimensional composite material.

[0087] Example 16: Preparation of Pt-SnNb2O6 / g-C3N5 three-dimensional composite material

[0088] Weigh 0.02 g of SnNb2O6 / g-C3N5 nanomaterial prepared in Example 6 and add it to 25 mL of H2O for ultrasonic mixing. Then add a certain amount of H2PtCl6·6H2O (10 mg·mL -1)The mixture was stirred for 4-10 h, then washed and collected to obtain a mixed solution and dried in vacuo. The obtained powder was calcined at 600 °C for 5 h in a mixed atmosphere of H2 and Ar2 (the volume ratio of H2 and Ar2 was 1:1), and the obtained powder was a Pt-SnNb2O6 / g-C3N5 three-dimensional composite material.

[0089] Example 17: Preparation of Co-SnNb2O6 / g-C3N5 three-dimensional composite material

[0090] 0.02 g of SnNb2O6 / g-C3N5 nanomaterial prepared in Example 6 was weighed and added to a mixed solution of 20 mL H2O and 10 mL triethanolamine. Then a certain amount of Co(NO3)2·6H2O (10 mg·mL -1) Add a certain amount of ethylene glycol. Then photo-deposit the mixed solution under vacuum for 2-5 h, then wash and collect the mixed solution and dry it. The obtained powder is the Co-SnNb2O6 / g-C3N5 three-dimensional composite material.

[0091] Example 18: Preparation of Fe-SnNb2O6 / g-C3N5 three-dimensional composite material

[0092] Weigh 0.02 g of the SnNb2O6 / g-C3N5 nanomaterial prepared in Example 6 and add it to a mixed solution of 20 mL H2O and 10 mL triethanolamine, then add a certain amount of ferric chloride solution to a certain amount of ethylene glycol. Then, the mixed solution is photodeposited under vacuum for 2-5 h, then washed, collected, and dried to obtain a mixed solution. The obtained powder is the Fe-SnNb2O6 / g-C3N5 three-dimensional composite material.

[0093] Example 19: Preparation of Pd-SnNb2O6 / g-C3N5 three-dimensional composite material

[0094] 0.02 g of the SnNb2O6 / g-C3N5 nanomaterial prepared in Example 6 was weighed and added to a mixed solution of 20 mL H2O and 10 mL triethanolamine, and then a certain amount of PdCl2 solution was added to a certain amount of ethylene glycol. The mixed solution was then photodeposited under vacuum for 2-5 h, and then washed, collected, and dried to obtain a mixed solution. The obtained powder was the Pd-SnNb2O6 / g-C3N5 three-dimensional composite material.

[0095] Example 20: Preparation of Cu-SnNb2O6 / g-C3N5 three-dimensional composite material

[0096] 0.02 g of the SnNb2O6 / g-C3N5 nanomaterial prepared in Example 6 was weighed and added to a mixed solution of 20 mL H2O and 10 mL triethanolamine, and then a certain amount of cupric acetate was added to a certain amount of ethylene glycol. The mixed solution was then photodeposited under vacuum for 2-5 h, and then washed, collected, and dried to obtain a mixed solution. The obtained powder was the Cu-SnNb2O6 / g-C3N5 three-dimensional composite material.

[0097] Example 17: Preparation of Ag-SnNb2O6 / g-C3N5 three-dimensional composite material

[0098] 0.02 g of SnNb2O6 / g-C3N5 nanomaterial prepared in Example 6 was weighed and added to a mixed solution of 20 mL H2O and 10 mL triethanolamine, and then a certain amount of AgNO3 solution was added to a certain amount of ethylene glycol. The mixed solution was then photodeposited under vacuum for 2-5 h, and then washed, collected, and dried to obtain a mixed solution. The obtained powder was the Ag-SnNb2O6 / g-C3N5 three-dimensional composite material.

[0099] Photocatalytic performance study

[0100] The photocatalytic performance of the g-C3N5 nanorods prepared in Example 1 and the SnNb2O6 / g-C3N5 nanocomposite materials prepared in Example 6 was studied, and the photocatalytic CO2 reduction performance of different materials under irradiation with a 300 W xenon lamp (equipped with a filter of λ≥420 nm) was tested; the specific operation is as follows:

[0101] 0.02 g of the photocatalyst prepared in the above examples or comparative examples, 10 mL of acetonitrile and 2 mL of H2O were added to a photocatalytic reactor and ultrasonically treated for 1-2 min, and then high-purity CO2 was introduced into the reactor for 30 min to remove residual air and perform leak detection;

[0102] The photocatalytic reaction bottle was placed under a xenon lamp and irradiated with N2 carrier gas. The gas generated after irradiation for 3 h was analyzed online and its content was determined using a gas chromatograph equipped with a TCD detector and a molecular sieve column.

[0103] As can be seen from the figure, the photocatalytic CO2 reduction performance of the SnNb2O6 / g-C3N5 nanocomposite material is higher than that of g-C3N5 and SnNb2O6. From the above photocatalytic test results, it can be seen that the SnNb2O6 / g-C3N5 nanocomposite material prepared by the present invention exhibits excellent visible light photocatalytic performance.

[0104] The photocatalytic performance of the g-C3N5 nanorods prepared in Example 1, the SnNb2O6 / g-C3N5 nanocomposite prepared in Example 6, the Pt-g-C3N5 nanocomposite prepared in Example 9, and the Pt-SnNb2O6 / g-C3N5 three-dimensional composite material prepared in Example 10 was studied, and the photocatalytic hydrogen evolution performance and photocatalytic CO2 reduction performance of different materials under irradiation with a 300 W xenon lamp (equipped with a filter of λ≥420 nm) were tested; the specific operation is as follows:

[0105] 0.02 g of the photocatalyst prepared in the above examples or comparative examples was ultrasonically dispersed in a mixed solution consisting of 40 mL of water and 10 mL of LTEOA for 1-2 min. Before irradiation, N2 was introduced for half an hour to remove residual air and perform leak detection;

[0106] The photocatalytic hydrogen evolution experiment was carried out at 25°C. Using N2 carrier gas, a gas chromatograph equipped with a TCD detector and a molecular sieve column was used to analyze the gas produced at an illumination interval of 1 h and determine its content;

[0107] 0.01 g of the photocatalyst prepared in the above examples or comparative examples was added to 10 mL H2O in a photocatalytic reactor and ultrasonically treated for 1-2 min, and then high-purity CO2 was introduced into the reactor for 30 min to remove residual air and perform leak detection;

[0108] The photocatalytic reaction bottle was placed under a xenon lamp and irradiated with N2 carrier gas. The gas generated after irradiation for 3 h was analyzed online and its content was determined using a gas chromatograph equipped with a TCD detector and a molecular sieve column.

[0109] As shown in Figures 1-8, the photocatalytic hydrogen evolution performance of the Pt-SnNb2O6 / g-C3N5 three-dimensional composite material is significantly higher than that of g-C3N5, SnNb2O6, SnNb2O6 / g-C3N5 and Pt-g-C3N5. In addition, the photocatalytic CO2 reduction performance of the Pt-SnNb2O6 / g-C3N5 nanocomposite material is higher than that of g-C3N5 and SnNb2O6 / g-C3N5. As shown in the above photocatalytic test results, the Pt-SnNb2O6 / g-C3N5 nanocomposite material prepared by the present invention exhibits excellent visible light photocatalytic performance.

[0110] The photocatalytic performance of the g-C3N5 nanorods prepared in Example 1 and the SnNb2O6 / g-C3N5 nanocomposite materials prepared in Example 6 was studied, and the photocatalytic degradation of organic pollutants and antibiotics of different materials under irradiation of a 300 W xenon lamp (equipped with a filter of λ≥420 nm) was tested; the specific operation is as follows:

[0111] Rhodamine B (RhB) and tetracycline (TC) were used as target degradation agents to investigate the photocatalytic performance of different samples. -1 ) and dilute to 100mL with water;

[0112] 0.05 g of the photocatalyst prepared in the above examples or comparative examples was added and mixed evenly by ultrasonication for 1-2 min, and a photocatalytic degradation experiment was carried out at 25° C.;

[0113] Before turning on the light, stir for 30 min in dark conditions to allow the photocatalyst to reach adsorption-desorption equilibrium on the target degradation agent;

[0114] The photocatalytic reaction bottle was placed under a xenon lamp, and then 5 mL of the suspension was taken for centrifugation every 20 min and the sample supernatant was taken for measurement. The absorbance values ​​at different reaction times were measured using a UV-visible spectrophotometer.

[0115] As can be seen from the figure, the photocatalytic hydrogen evolution performance of the Pt-SnNb2O6 / g-C3N5 three-dimensional composite material is significantly higher than that of g-C3N5, SnNb2O6, SnNb2O6 / g-C3N5 and Pt-g-C3N5. In addition, the photocatalytic CO2 reduction performance of the Pt-SnNb2O6 / g-C3N5 nanocomposite material is higher than that of g-C3N5 and SnNb2O6 / g-C3N5. From the above photocatalytic test results, it can be seen that the Pt-SnNb2O6 / g-C3N5 nanocomposite material prepared by the present invention exhibits excellent visible light photocatalytic performance.

[0116] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a three-dimensional SnNb2O6 / g-C3N5 composite material supported by a single atom catalyst, characterized in that: The following steps are involved: Preparation of g-C3N5 nanomaterials: (1) Weigh 1.5-2 g of 3-amino-1,2,4-triazole and add it to a NaCl solution, and stir evenly. The NaCl solution is 10-15 g of NaCl dissolved in 30-60 mL of H2O. (2) The mixed solution was then evaporated to dryness in a water bath at 80-100 °C and dried at 60-80 °C for 12-14 h to ensure that no water remained. The resulting white solid was then ground into powder and transferred to a muffle furnace at 10 °C min −1 The mixture was heated to 500-550°C at a heating rate of 1000 °C and kept at this temperature for 3-5 h, and then cooled naturally to room temperature; (3) The obtained brown product was washed alternately with ethanol and deionized water for multiple times to remove unreacted NaCl crystals and dried at 60 °C for 12 h. The obtained brown product was g-C3N5 nanomaterial; Preparation of SnNb2O6 / g-C3N5 nanomaterials: 0.01-0.08 g SnNb2O6 was added to 20-40 mL water and ultrasonicated for 30 min, then 0.2 g g-C3N5 nanorods were added and the mixed solution was stirred for 4-12 h and then transferred to a 200 mL hydrothermal reactor and hydrothermaled at 100-180°C for 10-12 h, then the mixed solution was collected by centrifugation and dried; the obtained powder was SnNb2O6 / g-C3N5 nanomaterial; Preparation of Pt-SnNb2O6 / g-C3N5 three-dimensional composite materials: Weigh 0.02 g SnNb2O6 / g-C3N5 nanomaterials into a mixed solution of 20 mL H2O and 10 mL triethanolamine, then add 10 mg mL -1 H2PtCl6·6H2O is added to ethylene glycol; the mixed solution is then photodeposited under vacuum for 2-5 hours, and then the mixed solution is washed, collected and dried; the obtained powder is the Pt-SnNb2O6 / g-C3N5 three-dimensional composite material.

2. A method for preparing a three-dimensional SnNb2O6 / g-C3N5 composite material supported by a single atom catalyst, characterized in that: The following steps are involved: Preparation of g-C3N5 nanomaterials: (1) Weigh 1.5-2 g of 3-amino-1,2,4-triazole and add it to a NaCl solution, and stir evenly. The NaCl solution is 10-15 g of NaCl dissolved in 30-60 mL of H2O. (2) The mixed solution was then evaporated to dryness in a water bath at 80-100 °C and dried at 60-80 °C for 12-14 h to ensure that no water remained. The resulting white solid was then ground into powder and transferred to a muffle furnace at 10 °C min −1 The mixture was heated to 500-550°C at a heating rate of 1000 °C and kept at this temperature for 3-5 h, and then cooled naturally to room temperature; (3) The obtained brown product was washed alternately with ethanol and deionized water for multiple times to remove unreacted NaCl crystals and dried at 60 °C for 12 h. The obtained brown product was g-C3N5 nanomaterial; Preparation of SnNb2O6 / g-C3N5 nanomaterials: 0.01-0.08 g SnNb2O6 was added to 20-40 mL water and ultrasonicated for 30 min, then 0.2 g g-C3N5 nanorods were added and the mixed solution was stirred for 4-12 h and then transferred to a 200 mL hydrothermal reactor and hydrothermaled at 100-180°C for 10-12 h, then the mixed solution was collected by centrifugation and dried; the obtained powder was SnNb2O6 / g-C3N5 nanomaterial; Preparation of Co-SnNb2O6 / g-C3N5 three-dimensional composite materials: Weigh 0.02 g SnNb2O6 / g-C3N5 nanomaterials into a mixed solution of 20 mL H2O and 10 mL triethanolamine, then add 10 mg mL -1 Co(NO3)2·6H2O is added to ethylene glycol; the mixed solution is then photodeposited under vacuum for 2-5 hours, and then the mixed solution is washed, collected and dried; the obtained powder is the Co-SnNb2O6 / g-C3N5 three-dimensional composite material.

3. A method for preparing a three-dimensional SnNb2O6 / g-C3N5 composite material supported by a single atom catalyst, characterized in that: The following steps are involved: Preparation of g-C3N5 nanomaterials: (1) Weigh 1.5-2 g of 3-amino-1,2,4-triazole and add it to a NaCl solution, and stir evenly. The NaCl solution is 10-15 g of NaCl dissolved in 30-60 mL of H2O. (2) The mixed solution was then evaporated to dryness in a water bath at 80-100 °C and dried at 60-80 °C for 12-14 h to ensure that no water remained. The resulting white solid was then ground into powder and transferred to a muffle furnace at 10 °C min −1 The mixture was heated to 500-550°C at a heating rate of 1000 °C and kept at this temperature for 3-5 h, and then cooled naturally to room temperature; (3) The obtained brown product was washed alternately with ethanol and deionized water for multiple times to remove unreacted NaCl crystals and dried at 60 °C for 12 h. The obtained brown product was g-C3N5 nanomaterial; Preparation of SnNb2O6 / g-C3N5 nanomaterials: 0.01-0.08 g SnNb2O6 was added to 20-40 mL water and ultrasonicated for 30 min, then 0.2 g g-C3N5 nanorods were added and the mixed solution was stirred for 4-12 h and then transferred to a 200 mL hydrothermal reactor and hydrothermaled at 100-180°C for 10-12 h, then the mixed solution was collected by centrifugation and dried; the obtained powder was SnNb2O6 / g-C3N5 nanomaterial; Preparation of Fe-SnNb2O6 / g-C3N5 three-dimensional composite materials: Weigh 0.02 g SnNb2O6 / g-C3N5 nanomaterial and add it to a mixed solution of 20 mL H2O and 10 mL triethanolamine, then add the ferric chloride solution into ethylene glycol; then photodeposit the mixed solution under vacuum for 2-5 h, then wash and collect the mixed solution and dry it; the obtained powder is the Fe-SnNb2O6 / g-C3N5 three-dimensional composite material.

4. A method for preparing a three-dimensional SnNb2O6 / g-C3N5 composite material supported by a single atom catalyst, characterized in that: The following steps are involved: Preparation of g-C3N5 nanomaterials: (1) Weigh 1.5-2 g of 3-amino-1,2,4-triazole and add it to a NaCl solution, and stir evenly. The NaCl solution is 10-15 g of NaCl dissolved in 30-60 mL of H2O. (2) The mixed solution was then evaporated to dryness in a water bath at 80-100 °C and dried at 60-80 °C for 12-14 h to ensure that no water remained. The resulting white solid was then ground into powder and transferred to a muffle furnace at 10 °C min −1 The mixture was heated to 500-550°C at a heating rate of 1000 °C and kept at this temperature for 3-5 h, and then cooled naturally to room temperature; (3) The obtained brown product was washed alternately with ethanol and deionized water for multiple times to remove unreacted NaCl crystals and dried at 60 °C for 12 h. The obtained brown product was g-C3N5 nanomaterial; Preparation of SnNb2O6 / g-C3N5 nanomaterials: 0.01-0.08 g SnNb2O6 was added to 20-40 mL water and ultrasonicated for 30 min, then 0.2 g g-C3N5 nanorods were added and the mixed solution was stirred for 4-12 h and then transferred to a 200 mL hydrothermal reactor and hydrothermaled at 100-180°C for 10-12 h, then the mixed solution was collected by centrifugation and dried; the obtained powder was SnNb2O6 / g-C3N5 nanomaterial; Preparation of Pd-SnNb2O6 / g-C3N5 three-dimensional composite materials: Weigh 0.02 g SnNb2O6 / g-C3N5 nanomaterial and add it to a mixed solution of 20 mL H2O and 10 mL triethanolamine, then add PdCl2 solution into ethylene glycol; then photodeposit the mixed solution under vacuum for 2-5 h, then wash and collect the mixed solution and dry it; the obtained powder is the Pd-SnNb2O6 / g-C3N5 three-dimensional composite material.

5. A method for preparing a three-dimensional SnNb2O6 / g-C3N5 composite material supported by a single atom catalyst, characterized in that: The following steps are involved: Preparation of g-C3N5 nanomaterials: (1) Weigh 1.5-2 g of 3-amino-1,2,4-triazole and add it to a NaCl solution, and stir evenly. The NaCl solution is 10-15 g of NaCl dissolved in 30-60 mL of H2O. (2) The mixed solution was then evaporated to dryness in a water bath at 80-100 °C and dried at 60-80 °C for 12-14 h to ensure that no water remained. The resulting white solid was then ground into powder and transferred to a muffle furnace at 10 °C min −1 The mixture was heated to 500-550°C at a heating rate of 1000 °C and kept at this temperature for 3-5 h, and then cooled naturally to room temperature; (3) The obtained brown product was washed alternately with ethanol and deionized water for multiple times to remove unreacted NaCl crystals and dried at 60 °C for 12 h. The obtained brown product was g-C3N5 nanomaterial; Preparation of SnNb2O6 / g-C3N5 nanomaterials: 0.01-0.08 g SnNb2O6 was added to 20-40 mL water and ultrasonicated for 30 min, then 0.2 g g-C3N5 nanorods were added and the mixed solution was stirred for 4-12 h and then transferred to a 200 mL hydrothermal reactor and hydrothermaled at 100-180°C for 10-12 h, then the mixed solution was collected by centrifugation and dried; the obtained powder was SnNb2O6 / g-C3N5 nanomaterial; Preparation of Cu-SnNb2O6 / g-C3N5 three-dimensional composite materials: 0.02 g SnNb2O6 / g-C3N5 nanomaterial was weighed and added to a mixed solution of 20 mL H2O and 10 mL triethanolamine, and then copper acetate was added to ethylene glycol; the mixed solution was then photodeposited under vacuum for 2-5 h, and then washed, collected, and dried to obtain the mixed solution; the obtained powder was the Cu-SnNb2O6 / g-C3N5 three-dimensional composite material.

6. A method for preparing a three-dimensional SnNb2O6 / g-C3N5 composite material supported by a single atom catalyst, characterized in that: The following steps are involved: Preparation of g-C3N5 nanomaterials: (1) Weigh 1.5-2 g of 3-amino-1,2,4-triazole and add it to a NaCl solution, and stir evenly. The NaCl solution is 10-15 g of NaCl dissolved in 30-60 mL of H2O. (2) The mixed solution was then evaporated to dryness in a water bath at 80-100 °C and dried at 60-80 °C for 12-14 h to ensure that no water remained. The resulting white solid was then ground into powder and transferred to a muffle furnace at 10 °C min −1 The mixture was heated to 500-550°C at a heating rate of 1000 °C and kept at this temperature for 3-5 h, and then cooled naturally to room temperature; (3) The obtained brown product was washed alternately with ethanol and deionized water for multiple times to remove unreacted NaCl crystals and dried at 60 °C for 12 h. The obtained brown product was g-C3N5 nanomaterial; Preparation of SnNb2O6 / g-C3N5 nanomaterials: 0.01-0.08 g SnNb2O6 was added to 20-40 mL water and ultrasonicated for 30 min, then 0.2 g g-C3N5 nanorods were added and the mixed solution was stirred for 4-12 h and then transferred to a 200 mL hydrothermal reactor and hydrothermaled at 100-180°C for 10-12 h, then the mixed solution was collected by centrifugation and dried; the obtained powder was SnNb2O6 / g-C3N5 nanomaterial; Preparation of Ag-SnNb2O6 / g-C3N5 three-dimensional composite materials: Weigh 0.02 g SnNb2O6 / g-C3N5 nanomaterial and add it to a mixed solution of 20 mL H2O and 10 mL triethanolamine, then add AgNO3 solution to ethylene glycol; then photodeposit the mixed solution under vacuum for 2-5 h, then wash and collect the mixed solution and dry it; the obtained powder is the Ag-SnNb2O6 / g-C3N5 three-dimensional composite material.

7. A single-atom catalyst-supported SnNb2O6 / g-C3N5 three-dimensional composite material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 6.

8. Application of the single-atom catalyst-supported SnNb2O6 / g-C3N5 three-dimensional composite material according to claim 7 in visible light photocatalysis.

Citation Information

Patent Citations

  • Preparation method of two-dimensional tungsten oxide / stannic niobate nanosheet-sheet composite material

    CN106881079A

  • Cobalt hydroxide / tin niobate composition material as well as preparation method and application thereof

    CN107790142A